Conference on prestressed concrete pressure vessels at Church House, Westminster, S.W.1, 13-17 March 1967 - Udall, Marilyn S. (Institution of Civil Engineers, 1968)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held on 13-17 March 1967.